Short-term adjusted outcomes for heart failure - Gabriele Messina; Silvia Forni; Francesca Collini; Antonello Galdo; Valeria Di Fabrizio; Nicola Nante (Heart International, 2016)
Purpose Heart failure (HF) is recognized as a major problem in industrialized countries. Short-term adjusted outcomes are indicators of quality for care process during/after hospitalization. Our aim is to evaluate, for patients with principal diagnosis of HF, in-hospital mortality and 30-day readmissions for all-causes using two different risk adjustment (RA) tools.